Fostering transparency among NPOs in Malaysia: A call for sustainability reporting (Global Business Management Review (GBMR), 2023)
The Non-Profit Organizations (NPOs) sector has recently been described as undergoing transparency crisis. However, amid calls for NPOs to be more transparent, there is little attempts from both practitioners, regulators and academicians moving towards sustainability reporting. Therefore, this paper aims to provide an understanding on the importance for NPOs to produce sustainability reporting. Using desktop research as method of gathering data, the paper deliberates the importance of sustainability reporting for NPOs in Malaysia. The paper conceptualizes the role of sustainability reporting as the way forward, towards building trust and confidence, thus fostering transparency in reporting among NPOs. This paper highlights the future relationship that the NPOs and other stakeholders like government and corporate organizations should focus on towards creating sustainable development. The findings contribute to improving NPOs transparency through sustainability reporting and fostering society rights in Malaysia.